Effect of steam pre-treatment on co-composting of oil palm empty fruit bunch - Che Hamzah, Nurul Husna (2017)
Palm oil mill effluent (POME) which is abundant in most palm oil mills is harmful to the surrounding environment. Methane gas emission during POME open pond treatment contributes to the global warming effect. However, the nutrient in POME could be utilized by co-composting with oil palm empty fruit bunches (OPEFB). Conventional mulching of OPEFB takes about 6 to 12 months while current controlled composting takes 50–90 days to mature. This study aims to produce an accelerated composting treatment by treating shredded OPEFB with steam pre-treatment and raw POME as acid pre-treatment prior to composting. Two baseline composting studies were conducted in 80 days. The first baseline study examined the effect of steam pre-treatment, while the second baseline study examined the effect of raw POME as acid pre-treatment on OPEFB. The final composting treatments were selected from both baseline studies that have highly significant effects in temperature, C/N ratio, and tensile strength properties. The composting treatments were performed under a roofed area near the Machinery Design Laboratory in the Faculty of Engineering, Universiti Putra Malaysia. The compost was placed in plastic drums, which were regularly turned for aeration purpose. The compost mixtures were also monitored for temperature, moisture content, oxygen content, C/N ratio, and fibers tensile strength. Carbon to nitrogen (C/N) ratio is the main parameter measured in this study because it indicates the maturity of compost. The compost C/N ratio has reduced to below than 20 and accelerated to about 40 days of composting by pre-treatment with steam and raw POME. On the 40th day, the C/N ratio of all composting treatments have achieved lower than 20 of C/N ratio where the C/N ratio of steam treated-soaked OPEFB, steam treated OPEFB co-composted with chicken manure, steam treated OPEFB co-composted with anaerobic POME, and non-steam treated OPEFB co-composted with anaerobic POME are 17.7, 10.1, 13.8, and 15.6, respectively. The treatment of steam treated OPEFB co-composted with chicken manure has the lowest final C/N ratio and mean tensile strength, which indicates fast maturity and physical degradation of fibers. The tensile strength of steam-treated OPEFB co-composted with chicken manure (31.67 N/mm2) and soaked OPEFB co-composted with chicken manure (33.86 N/mm2) showed lower mean tensile strength compared to other compost treatments especially with non-steam-treated OPEFB co-composted with POME (37.68 N/mm2). Scanning Electron Microscopy (SEM) observations showed the presence of crack around the silica bodies while some fibers showed a rupture on the fiber's surface. Fibers from treatment steam-treated OPEFB co-composted with chicken manure showed a removal of silica bodies and more remaining holes compared to other compost treatments.